Islamic microfinance: the challenge of institutional diversity - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2007)
Forays into Islamic microfinance have been few and scattered and of limited outreach. Some have been mandated by the state, but lack popular demand, as in Iran; other have emerged in response to popular demand, but lack regulatory support by the state, as in Syria. This has provided the background for a more systematic study of Islamic microfinance in Indonesia, the largest Muslim country, where several strands of Islamic microfinance, formal and semiformal, have evolved since 1990 in parallel. Islamic banking is now officially recognized as part of a dual banking system in Indonesia. Lacking broad popular demand, experience differs by sub-sector: Only commercial banks have successfully acquired the art of Islamic banking by training young and dynamic people, yet lack experience in microfinance. Islamic rural banks, mostly under absentee ownership, have failed to prove themselves as efficient and dynamic providers of microfinance services. Unsupervised Islamic, like conventional, cooperatives are an outright menace to their members, who risk loosing their savings. There are two options of promoting Islamic microfinance: (1) Assisting Islamic commercial banks to establish units with Islamic microfinance products; (2) reassessing in a participatory process the challenges and realistic opportunities of Islamic rural banks and cooperatives, with a focus on effective internal control, external supervision, and the establishment of associations with apex services to their member institutions.
Keywords: 330; Islamische Bank; Mikrofinanzierung; Wirtschaftsförderung; Bankenpolitik; Indonesien